Environmental education for the isolated tribe (Anak Dalam) community in Jambi Province on conservation and environmental sanitation - Novanda, Ramazani (Journal of Character and Environment, 2025)
Background: Suku Anak Dalam or commonly called Suku Anak Dalamare a community group who still adheres the traditions. Their life that depends on the forest makes them need to protect and preserve the forest where they live. This research aims to examine the environmental education of Suku Anak Dalam related to their environmental conservation and sanitation. Methods: This study used a qualitative-descriptive approach, with an ethnographic research design. The research informants were 10 people consisting of the Suku Anak Dalam and the outer community. Then the questionnaire distributed to 15 students who are of Suku Anak Dalam ethnic. Data analysis techniques are generally used in qualitative research, and added purposive sampling to analyze the samples that have been determined. Findings: The results show that Suku Anak Dalamin Nagasari Village use Traditional Law, namely the Seleko Adat, which presents local wisdom values to preserving the environment by referring to traditional law that obtained from generation to generation. The typical way of Suku Anak Dalam community in preserving the environment is variety. First, they have to plant 2 trees when the child born. Second, taking care of the environment, because Gods will be angry, example they would not use soap and they not defecate in the river. Third, enforcing Traditional law, because stricter than religious and state law. environmental conservation and sanitation knowledge is carried out from daily activities. Conclusion: Daily necessities such as bathing using bidaro leaves and urang aring leaves, washing in the river but not using detergent soap. They do not defecate into the river, but they have a toilet that located about 10 metres from the river. Novelty/Originality of this article: The novelty of this research lies in exploring how the Suku Anak Dalam community integrates traditional laws and daily practices into environmental conservation and sanitation, offering unique insights into their sustainable lifestyle.